Characterization of the seascape used by juvenile and wintering adult Southern Giant Petrels from Patagonia Argentina - Blanco, Gabriela Silvina; Pisoni, Juan Pablo; Quintana, Flavio Roberto (Estuarine, Coastal and Shelf Science)
The characterization of the seascape used by marine top predators provides a wide perspective of pelagic habitat use and it is necessary to understand the functioning of marine systems. The goal of this study was to characterize the oceanographic and biological features of marine areas used by adult and first year juvenile southern giant petrels (SGP, Macronectes giganteus) from northern Patagonian colonies (Isla Arce and Gran Robredo) during the austral fall and winter (2005, 2006, 2007, and 2008). The marine environment exploited by the SGP was characterized using sea surface temperature (SST), SST gradients, chlorophyll-a concentration, water depth, oceanographic regimes, and ocean surface winds. In addition, the biological seascape was defined by considering the distribution of squid during the months of study. Juveniles SGP exploited a wide range of environments focusing mainly on productive neritic waters using a variety of oceanographic regimes. Juveniles were exposed to eutrophic and enriched waters, probably because of the frequent presence of thermal fronts in their utilization areas. Adults´ environments lacked of thermal fronts remaining the majority of their time within the oceanographic regime "Continental Shelf", in water depths of 100-200 m, exploiting mesotrophic and eutrophic environments, and remaining in areas of known food resources related to the presence of squid. For the most part, juveniles were exposed to westerly winds, which may have helped them in their initial flight to the shelf break, east of the colony. Wintering adults SGP also explored areas characterized by westerly winds but this did not play a primary role in the selection of their residence areas. Juveniles during their first year at sea have to search for food exploring a variety of unknown environments. During their search, they remained in productive environments associated to fronts and probably also associated to fisheries operating in their foraging areas. The understanding of pelagic birds´ habitat selection and ...